2012
DOI: 10.1038/jhg.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genetic polymorphisms of drug transporters, SLCO1B1, SLCO1B3 and ABCC2, in African-Americans, Hispanics and Caucasians and olmesartan exposure

Abstract: It has been reported that organic anion-transporting polypeptide (OATP) 1B1, OATP1B3 and multidrug resistance-associated protein 2 are involved in the hepatobiliary transport of olmesartan. We investigated the association of SLCO1B1, SLCO1B3 and ABCC2 polymorphisms with the pharmacokinetics of olmesartan. We sequenced all exons, exon-intron junctions and the 5 0 and 3 0 flanking regions of the three genes in 115 individuals from African-American, Hispanic and Caucasian populations who had participated in our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…A functional study of rs4149117 and rs7311358 in SLCO1B3 had been performed (Letschert et al, 2004), but individuals carrying SLCO1B3 SNPs in clinical trials were not involved with no phenotypic consequences for the pharmacokinetics . The distribution of a nonsynonymous SLCO1B3 SNP (rs12299012, V560A) in the present study was only observed in the AA subjects, which was consistent with previous screening studies for multiple ethnic groups (Endo et al, 2012;Schwarz et al, 2011). Among additional SLCO1B3 SNPs, a GWAS in a Korean population showed that rs2417940 in SLCO1B3 was significantly associated with serum bilirubin levels (Kang et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A functional study of rs4149117 and rs7311358 in SLCO1B3 had been performed (Letschert et al, 2004), but individuals carrying SLCO1B3 SNPs in clinical trials were not involved with no phenotypic consequences for the pharmacokinetics . The distribution of a nonsynonymous SLCO1B3 SNP (rs12299012, V560A) in the present study was only observed in the AA subjects, which was consistent with previous screening studies for multiple ethnic groups (Endo et al, 2012;Schwarz et al, 2011). Among additional SLCO1B3 SNPs, a GWAS in a Korean population showed that rs2417940 in SLCO1B3 was significantly associated with serum bilirubin levels (Kang et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…SLCO1B1 and SLCO1B3 SNPs were evaluated in multiple ethnic populations, but not in Asian populations (Endo et al, 2012), and the distribution of SLCO1B3 SNPs based on interethnic differences was investigated (Smith et al, 2007). A comparison of the genotype frequencies of SLCO2B1 rs12422149 in different ethnic groups was investigated between Japanese prostate cancer patients and other ethnic groups using published data (Fujimoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…79) No dramatic difference were found with olmesartan pharmacokinetics and OATP1B3 genetic variation following extensive sequencing of SLCO1B3. 80) The SNPs c.334T>G and c.699G>A were found to be associated with pharmacokinetics of mycophenolic acid, whereby exposure among variant carriers were significantly higher compared to wild type renal transplant patients. 81) However, more recently, Picard et al found the opposite trend in renal transplant patients.…”
Section: Oatp1b3mentioning
confidence: 99%
“…Other investigators did not confirm a role for polymorphisms in the SLCO1B1 gene and did not detect one for those in the gene encoding breast cancer resistance protein, ABCG2, but found that two singlenucleotide polymorphisms in the gene encoding mrp2, ABCC2, were associated with a greater olmesartan exposure . A later study from the group originally reporting on a role for SLCO1B1 gene polymorphisms in three ethnic groups also failed to confirm a role in olmesartan exposure and also did not detect one for polymorphisms in the genes encoding OATP1B3 or mrp2 (Endo et al, 2012).…”
Section: H Pharmacokinetic Pharmacogenomicsmentioning
confidence: 99%